Therapeutic Bispecific T-Cell Engager Antibody Targeting the Transferrin Receptor - Fu, Mingpeng; He, Qi; Guo, Zilong; Zhou, Xiaoran; Li, Heli; Zhao, Liang; Tang, Hongling; Zhou, Xiaoqi; Zhu, Huifen; Shen, Guanxin; He, Yong; Lei, Ping (Frontiers in Immunology, 2019)
Bispecific T-cell engager antibodies (BiTE) have been explored as a means to recruit cytolytic T cells to kill tumor cells. The transferrin receptor (TfR) is highly expressed on the surface of rapidly proliferating tumor cells. Therefore, it holds great potential in T cell redirecting therapies. In this paper, we developed a BiTE targeting TfR and CD3 (TfR-BiTE) and studied its therapeutic impact on TfR-positive cancer. TfR-BiTE had the ability to induce the selective lysis of various TfR-positive cancer cells through the activation of T cells, the release of cytokines, and then the coming proliferation of T cells, whereas TfR-negative cells were not affected. In a subcutaneous HepG2 xenograft model, low concentrations of TfR-BiTE inhibited tumor growth. Taken together, these results reveal that TfR-BiTE can selectively deplete TfR-positive HepG2 cells; hence, it represents a novel immunotherapeutic approach for the treatment of hepatocellular carcinoma.